How to Early Identify and Prevent the SARS-CoV-2 Infection in Children for Families? - Qiao, Meng-Yuan; Chen, Na; Zou, Xian; Mao, Dan-Hua; Cui, Hong-Tao; Li, Wei-Bin; Miao, Jing-Kun; Chen, Qi-Xiong (Frontiers in Pediatrics, 2020)
Importance: COVID-19 has become a worldwide pandemic. Many countries have reported cases of infection in children and newborns, and there is a trend of significantly increasing infections among these populations. Therefore, it is important to provide advice and guidance for the prevention and control of COVID-19 in children. Observations: Children are as susceptible to SARS-CoV-2 infection as adults. The manifestations in children are atypical, and children are much less likely to have critical cases. If children are infected, they may play an important role in the spread of SARS-CoV-2 because their symptoms are less obvious and less likely to be detected. To prevent COVID-19 from spreading among children, efforts to prevent and control the infection should be increased by controlling the source of infection, blocking the route of transmission and protecting the susceptible population. Conclusions and Relevance: The early identification of the COVID-19 in children and the protection of families are important measures to prevent the continued spread of SARS-CoV-2.